Pelaksanaan Pembelajaran Apresiasi Keberagaman Lagu Daerah di SMP Pembangunan Laboratorium UNP - Waruwu, Cici Putri Susanti; Jagar Lumbantoruan (Universitas Negeri Padang, 2024)
This study aims to determine and describe how the implementation of learning appreciation of the diversity of regional songs in class VIII B SMP Pembangunan Laboratorium UNP. This research uses qualitative methods with a descriptive approach. The research instrument is the researcher himself as the main instrument and supporting instruments such as stationery and cellphones. Data collection was carried out through the stages of literature study, observation, interviews and documentation. Data analysis techniques are carried out by collecting data, classifying data, clarifying data, analyzing data, describing and concluding. The results showed that lesson planning carried out by teachers was not fully guided by teaching modules that focused on learning objectives and were formulated in the flow of learning objectives. This makes the learning process has not been carried out optimally because the learning flow is not systematic. The approach method used by the teacher is conventional, leading to the lecture method and not varied in each meeting. Furthermore, the summative assessment results show that there are still students who do not understand the material of appreciation of the diversity of regional songs.